SALES OF LOCAL GOODS TO THE INTERNATIONAL MARKET - Lia Yulia; Nina Herlina; Purnama Sari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
One of the mainstay products of Tasikmalaya City is Kelom Geulis. Kelom Geulis is taken from the Dutch "Kelompen" which means wooden sandals. While "Geulis" comes from the Sundanese language which means beautiful. Kelom Geulis crafts or beautiful wooden sandals are widely produced in Tamansari Gobras Village, Tasikmalaya City. Kelom Geulis Tasikmalaya has been exported to Southeast Asia, Korea, Japan, Africa, Panama, the Middle East and parts of Europe. However, currently, the existence of a global market has an impact on reducing interest in domestic products, one of which is Kelom Geulis. Kelom Geulis, which is a characteristic of Tasikmalaya City, should be developed to become a superior product that can bring Tasikmalaya culture to the international level. The purpose of this study was to determine the impact of the global market on the level of sales of kelom geulis in Tasikmalaya city. The location of the study was conducted in Tasikmalaya City, the focus of the study was in the village of Tamansari Gobras Tasikmalaya. Primary data sources obtained from field observations and interviews with sources. While secondary data has sources from archives, personal documents and official documents. Data collection methods and techniques in the form of interviews , documentation and observations using research instruments in the form of interview guidelines and field notes. Data analysis in this study by reducing data, presenting data, analyzing and interpreting data.